A case study analysis : Johor Corporation / Adnan Aziz and Fairul Azni Jaafar - Aziz, Adnan; Jaafar, Fairul Azni (Faculty of Business and Management, 2001)
Johor Corporation ( Jcorp ) was incorporated under the Johor State Economic Development Corporation Enactment No. 4, 1968 ( Amendment 5, 1995 ) as a development agency and public enterprise. The Corporation is principally engaged in developing land for the purposes of industrial, agricultural, property, logging and in corporate activities. Its been called Johor State Economic Development Corporation was designed its establishment to break away from bureaucratic binds of a regular government department and to become a commercially-oriented investment arm of the Johor State Government. Within the context of Malaysia's New Economic Policy that has been launched in 1970, Jcorp. was been assigned with the responsibility of making a success of the Government's affirmative action program so vital to the nation's need to sustain social harmony and political stability.